Πρόσωπα και ιδέες στο σημερινό Βόλο - Επιθυμιάδης, Βασίλης ([χ.ό.], 1959)
Κίτσος Μακρής -- Λεφτέρης Ραφτόπουλος -- Βαγγέλης Σκουβαράς -- Δημήτριος Κασαβέτης -- Παυσανίας Γκάλιος -- Σταύρος Βασαρδάνης -- Κωστής Λάμπρου -- Καλλιόπη Πάντου -- Έρση Σαράτση -- Επιλογικά